2014
DOI: 10.4102/sajhrm.v12i1.647
|View full text |Cite
|
Sign up to set email alerts
|

Understanding talent attraction: The influence of financial rewards elements on perceived job attractiveness

Abstract: Orientation: In order to attract knowledge workers and maintain a competitive advantage,it is necessary for organisations to understand how knowledge workers are attracted todifferent types and levels of financial rewards.Research purpose: This research investigated a set of financial reward elements (remuneration, employee benefits and variable pay) to determine whether knowledgeworkers perceived them as attractive inducements when considering a job or position.Motivation for the study: In South Africa there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 20 publications
3
26
0
1
Order By: Relevance
“…For example, a research conducted by Skrickienė et al (2018) evaluated the education and training on an organizational level as the most effective, group and team level education as less effective and individual education as least effective. Unfortunately, the research indicated that employees educated and developed themselves primarily based on their own decision, as their organisations often did not provide them with sufficient motivations and stimuli (Schlechter et al, 2014;Hoole & Hotz, 2016;Tansley et al, 2016). Of course, employees are responsible for their improvement as well, however, employee education and training should firstly be a part of organization's strategic development (Vveinhardt & Minkutė-Henrickson, 2015), consolidated in the organization's values, plans and daily operations (Beirat et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, a research conducted by Skrickienė et al (2018) evaluated the education and training on an organizational level as the most effective, group and team level education as less effective and individual education as least effective. Unfortunately, the research indicated that employees educated and developed themselves primarily based on their own decision, as their organisations often did not provide them with sufficient motivations and stimuli (Schlechter et al, 2014;Hoole & Hotz, 2016;Tansley et al, 2016). Of course, employees are responsible for their improvement as well, however, employee education and training should firstly be a part of organization's strategic development (Vveinhardt & Minkutė-Henrickson, 2015), consolidated in the organization's values, plans and daily operations (Beirat et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Employee loyalty is found when employees are able to talk about their organisation to their friends, and portray it as a great organisation to work for (Antoncic and Antoncic, 2011) Remuneration Schlechter, Hung and Bussin (2014) …”
Section: Employee Loyaltymentioning
confidence: 99%
“…An organisation's ability to attract and retain the best talent is therefore one of the most important determinants of organisational effectiveness (Armstrong, 2006;Kehinde, 2012;Singh & Finn, 2003). Those organisations that differentiate themselves in their attraction, development and retention strategies are the ones that ultimately succeed (Al Ariss, Cascio & Paauwe, 2014;Schlechter et al, 2014;Tarique & Schuler, 2010).…”
Section: Research Purposementioning
confidence: 99%
“…In the current business environment, organisations are facing significant challenges in finding the correct employees (Schlechter et al, 2014). The term 'competency deficit' is used to describe what can be seen as one of the reasons why organisations are facing these challenges in the attraction of talented employees (Herman, Olivio & Gioia, 2003).…”
Section: Research Purposementioning
confidence: 99%
See 1 more Smart Citation